Elevated Systemic and Intestinal Inflammatory Response Are Associated With Gut Microbiome Disorder After Cardiovascular Surgery - Xia, Xiong; Ni, Jiangjin; Yin, Shengnan; Yang, Zhipeng; Jiang, Haini; Wang, Chao; Peng, Jian; Wei, Hongkui; Wang, Xingyu (Frontiers in Microbiology, 2021)
Systemic inflammatory response post cardiovascular surgery is associated with poor prognosis, to which gut barrier impairment is related. To address whether perioperative changes of gut microbiome is associated with gut dysbiosis and systemic inflammatory response, we examined changes of gut microbiome, gut dysbiosis and systemic inflammatory response in cardiovascular patients prior to (Pre) surgery, and on the first defecation day (Po1) or a week (Po2) post-surgery. Markedly enhanced systemic inflammatory response was observed in Po1 and Po2 compared with that in Pre. In line with inflammatory response, impaired gut barrier and elevated gut local inflammation were observed in Po1 and Po2. Microbiome analysis showed remarkably steadily decline of alpha diversity peri-operatively. In addition, microbial composition in post-operation period was characterized with significant expansion of Enterococcus combined with a decrease in anaerobes (Blautia, Faecalibacterium, Bifidobacterium, Roseburia, Gemmiger, [Ruminococcus], and Coprococcus), which were typically health-associated bacteria. Spearman correlation analysis showed microbiome disorder was associated with enhanced systemic inflammatory response and gut dysbiosis. These results suggested that microbiome dysbiosis contributed to disturbed gut homeostatic and subsequent elevated plasma endotoxin and systemic inflammatory response after cardiovascular surgery. Gut microbiome would be considered as an essential target for improving prognosis in future clinical intervention.